Self-esteem, social competence, personality and glossophobia among Nigerian undergraduates (2021)
Expression of self in the public is relevant to human relationship, social connect and help seeking and survival. However, glossophobia holds a confederation of complex issues, particularly social and health ones. It is capable of averting loneliness, anger, psychological withdrawal, aggression, emotional maladjustment, anomie and suicide ideation. This propelled investigation on the psycho-social factors as tools for glossophobia among Nigeria undergraduates in Oyo State, Nigeria. Descriptive design of the correlational type was employed. A sample of 300 undergraduate students was randomly selected from three universities. Four reliable measuring scales (Speaking Anxiety; a = 0.88, Personality scale; a — 0.82, Self-esteem; a = 0.84, and Social competence; a. — 0.79) were used for data collection. Pearson Product Moment Correlation (PPMC) and multiple linear regression analysis were used to analyse the data at 0.05 level of significance. It was discovered that glossophobia negatively correlated with selfesteem (r- -0.309, p<0.05), social competence (r= -0.402) and personality (r= -0.202). Multiple regression analysis revealed that there was a significant joint contribution of self-esteem, social competence and personality to glossophobia. The most potent predictors of glossophobia were social competence (Beta = -.243, t = -4.817), and self-esteem (Beta = - .211, t = -3.877). Personality (Beta = -.036, t = -.667) was not a potent predictor of glossophobia. This implies that self-esteem, social competence and personality will reduce glossophobia by 18.9%, 24.4% and 42%o, respectively. University managements should include diagnoses of undergraduates' glossophobia status as part of registration procedure to identify candidate who need urgent psychotherapeutic intervention. Undergraduate students should be helped in improving their self esteem so as to boost their self-worth when faced with need to speak or connect with other people. Since students cannot live in isolation in their effort to meet academic demands, lecturers should help them build social competence through giving group assignments.